Central office foci and principal data use: A comparative study of equity-focused practice in six districts - Roegman, Rachel (Education Policy Analysis Archives, 2020)
In this comparative study, I examine principal data use in two sets of districts. One set of three districts has a district-wide focus on using data to improve instruction, and the other set, also with three districts, has a district-wide focus on analyzing disaggregated data by student demographic groups. Data sources include interviews with principals in each set (18 from data-focused districts, and 9 from disaggregation-focused districts), and analysis focuses on ways that they talk about analyzing data in relation to district expectations and equity. Findings showed that each set of principals shared a different approach to data, either performance-focused or demographic-focused, suggesting the central role of the district in guiding how data are used at the building level. I conclude with implications for practice, policy, and research.